A SWOT Analysis of the Role of the Jaffna Archaeological Museums in the Development of Cultural Tourism - Sajitharan, S. (University of Jaffna, 2023)
In developing countries, cultural tourism means promoting the traditional cultural heritage. Thus, museums contribute greatly towards the promotion of cultural tourism and have become an intrinsic part of it. Visitors of museum have a strong link to tourism since tourists are part of the museum visitors. Museums function as organized resources of cultural tourism. They are repositories of collected items of cultural heritage, where they are preserved after deep research in order to exhibit them to the public. Its main functions are acquisition, preservation, education and exhibition of cultural objects of great value. The role of museums in cultural tourism is remarkable; they reflect the heritage of a region or country. The museums are really treasure houses that protect the cultural heritage. Because of this aspect, there is great demand for museums among tourists. In developing countries like Sri Lanka, most visitors to these museums are tourists. This research is concerned with the role of the Jaffna archaeological museum in the development of cultural tourism in Northern Sri Lanka. The Jaffna archaeological museum is a predominant cultural resource and a prominent tourist attraction in Northern Sri Lanka. It consists of many collections of cultural heritage. This museum is the first archaeological museum of Northern Sri Lanka. Till now it has functioned as the museum that preserves elements related to the history of Jaffna. The records of this museum reveal that the collection of items started in 1946 and recording started in 1947. Hence it is an important cultural institution and also an important cultural resource in Sri Lanka's tourism industries. The goal of this research can be reached by revealing the internal strength and weakness and the external opportunities and threats of Jaffna archaeological museum.
Keywords: Jaffna archaeological museum; Cultural tourism; Cultural heritage; Archaeological artifacts and SWOT analysis